STUDI KUALITATIF TENTANG STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN MENULIS MELALUI PENDEKATAN KONTEKSTUAL SISWA DI SEKOLAH DASAR. - Aminah Putri Afisa; Ichda Wahyuni, Holy; Setiawan, Fajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify teachers’ strategies in developing the writing skills of third-grade elementary school students through a contextual teaching and learning approach. The research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with third-grade teachers, and documentation of students’ written work. Data analysis was conducted descriptively through the stages of data reduction, data display, and conclusion drawing, with data validity strengthened through source and technique triangulation. The results indicate that the contextual approach was implemented through individual teacher guidance, assistance in writing digraphs such as ng and ny, and correction of errors in letter and word writing. The application of these strategies helped students develop ideas based on real-life experiences, increase their motivation to write, and improve their ability to construct sentences and paragraphs coherently. Thus, the contextual approach makes writing instruction more meaningful and can be used as an alternative to strengthen basic literacy in elementary school students. Keywords: contextual approach, writing skills, teacher strategies.